Climate, agroecology, and farm returns: differential impacts with implications for agricultural progress in the face of climate change - Mbiafeu, Marlene Francine; Molua, Ernest L.; Sotamenou, Joel; Ndip, Francis E. (Frontiers in Sustainable Food Systems, 2024)
Climate change is expected to have differential impacts on different zones. In this study, we employed the Ricardian technique, estimated through ordinary least squares (OLS) to assess the impact of climate change on farmers' revenue. We use survey data from two distinct agroecological zones in Cameroon. Our results show that rainfall is the main climatic variable affecting farmers' revenue. The results are statistically different for the two agroecological zones. While rainfall in the dry season affects revenue in the western highland zone. No climatic variable seems to affect farm revenue in the bimodal forest zone. These results suggest that the abundance of forest in the bimodal zone maybe be shielding the zone from the effects of climate change. We therefore recommend that farmers employ water harvesting and lowcost irrigation methods to cope with changes in rainfall pattern especially in extended dry seasons. Facilitating farmers' access to climate information particularly with respect to the onset and cessation of rains will improve planning farming operations.